PROTOTYPE RANCANGAN PRINTER 3D DENGAN SMART LCD BERBASIS ARDUINO MEGA 2560 MENGGUNAKAN TEKNOLOGI FUSED FILAMENT FABRICATION - Marcell Petrus Saptono; Romdani Paris Fuad (LPPM Poltek ST Paul, 2020)
In the development of industrial system 4.0 one of which sustains the development is 3D Printing technology. The purpose of this research is to design a 3D Printer machine with an Arduino MEGA 2560 Microcontroller, RAMPS 1.4 Shield, NEMA 17 stepper motor, DVR8825 motor driver, PLament Filament, E3D v6 HotEnd, Memory Card, Smart LCD. Construction of the framework of the design of the 3D Printing tool by assembling the frame of the 3D printing machine, the 3D Machine Stepper Motor, the XYZ Limit Endstop, the exstruder mount, the bed holder, the HotEnd assembly for the heater heater. The printing process can be connected to a PC or using memory card support, and operating instructions are displayed on the LCD monitor. This research produces an Arduino-based 3D printer with FFF (Fused Filament Fabrication) technology that will make it easier for users to operate a 3D printer with an LCD screen and Printing does not have to always be connected with a PC because it uses a memory card that can store files and produce better printing. This research uses the Linear Sequential Model (LSM) research method. This model is often called the